Systemic Risk: Cause or Effect of the Financial Crisis in the Euro Area? The Case of Spanish Banking System Bailouts - Santos, Juan Luis; Kaszowska, Jagoda (Olsztyn Economic Journal, 2018)
The aim of this paper is to determine to which extent systemic risk is a cause and an effect of the 2008 financial crisis. In the context of Spanish bailouts, we study the transmission of risk in the Spanish banking system. We make use of data from Google Trends on all Spanish financial institutions, which are selected as examples of one of the countries most affected in the last financial crisis. This analysis is one of the first attempts to use this kind of data for purposes of financial analysis. We compute the impact of each bailout in the banking system and we show how it affects the activity of the bailed-out bank and other institutions according to their status both before and after the announcement of the bailouts. We then show that it is possible to quantify the subjective systemic risk, an elusive concept that is difficult to measure with data from standard sources.